2020
DOI: 10.3390/app10144905
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Analytical Approach to Predict the Determinants of Cloud Computing Adoption in Higher Education Institutions

Abstract: Cloud computing (CC) delivers services for organizations, particularly for higher education institutions (HEIs) anywhere and anytime, based on scalability and pay-per-use approach. Examining the factors influencing the decision-makers’ intention towards adopting CC plays an essential role in HEIs. Therefore, this study aimed to understand and predict the key determinants that drive managerial decision-makers’ perspectives for adopting this technology. The data were gathered from 134 institutional managers, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 167 publications
1
19
0
Order By: Relevance
“…Accordingly, the items of DV3, ICC2, LC2, LC3, and LC4 were adequate to complement with the threshold value of AVE and CR [70,77]. That is, all the five constructs met the threshold values/minimum cut-off values for CR and AVE, since all CRs were greater than 0.7 and all AVEs were greater than 0.5 [70,78]. It was concluded that the constructs meet reliability and convergent validity requirements at this stage.…”
Section: Measurement Modelmentioning
confidence: 99%
“…Accordingly, the items of DV3, ICC2, LC2, LC3, and LC4 were adequate to complement with the threshold value of AVE and CR [70,77]. That is, all the five constructs met the threshold values/minimum cut-off values for CR and AVE, since all CRs were greater than 0.7 and all AVEs were greater than 0.5 [70,78]. It was concluded that the constructs meet reliability and convergent validity requirements at this stage.…”
Section: Measurement Modelmentioning
confidence: 99%
“…However, ANN is ineffective at testing hypotheses and establishing causal relationships due to its "black-box" character (Liébana-Cabanillas et al, 2017). Thus, similar to existing studies (Sharma et al, 2016;Li et al, 2019;Qasem et al, 2020), this work applied ANN as the second stage analysis technique. Three layers comprise the application of the ANN method: "input layer," "hidden layer," and "output layer."…”
Section: Neural Network Analysismentioning
confidence: 95%
“…Similarly, many researchers have combined ANN and PLS-SEM analysis in a variety of contexts. These include CRM adoption (Ahani et al, 2017), motivators of cloud computing (Sharma et al, 2016), wearable healthcare device and iOS adoption (Chong & Bai, 2014), mobile social media use intention in emergencies (Li et al, 2019), and determinant of cloud computing (Qasem et al, 2020). As a result, this revisits the SMCCR model and ascertains the elements that significantly impact resilience via ANN analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A) Refers to provider operations that have a substantial impact on the likelihood of continuing to use cloud computing. Questionaire have been adapted from (Qasem et al, 2020). The data has been collected from 280 IT-persons of different healthcare centers.…”
Section: Vendor Assistance (Vs)mentioning
confidence: 99%